An overview of the sheep research activities in the highlands - Akalework, N.; Kabaija, E. (International Livestock Centre for Africa, 1988)
Gives an overview of the sheep research activities in the highlands of Ethiopia with particular reference to monitoring work performance and mineral supplementation.